Comparative study of magnesium sulphate nebulization and lignocaine nebulization in prevention of postoperative sore throat (POST) - Gopal Sharma; Kumar Asnani; Sanjay Kalani; Mohit Kumar (Creative Pharma Assent, 2023)
Background: General anaesthesia (GA) includes intubation a necessary step to provide adequate ventilation in patients under anaesthesia along with protection of airway from regurgitation and aspiration. Postoperative sore throat (POST), hoarseness of voice, cough are common sequelae. The present study compares the efficiency of preoperative nebulization of lignocaine hydrochloride and magnesium sulphate for reducing the incidence of POST in patients under GA. Methods: The study conducted in GMC Kota and attached hospitals on 100 patients of surgery duration one hour to three hours. Patients were randomly allocated in two groups Lignocaine group and Magnesium group. Results: The majority of patients belonged to the age between 40 and 70 years. There was no significant difference in the mean pulse rate, SBP, mean SpO2. Comparison of sore throat in both the groups at rest, just after extubation, 2 hours, 8 hours, 24 hours and 48 hours showed incidence more common in lignocaine group than magnesium group but no significant difference (P>0.05). Hoarsness after extubation reduced within 24 hours in Magnesium group in comparison to Lignocaine group where it persists till 48 hrs. Conclusion: Incidence of sore throat, hoarseness of voice and cough was more common in lignocaine group and more in female patients. Both drugs can be used for prevention of postoperative sore throat, but magnesium sulphate has better results.